Love And Hope Reflected In Gayle Forman's If I Stay Novel (2009):An Individual Psychological Approach - Wahyuni, Sri; Titis Setyabudi, Titis Setyabudi, S.S.,M.Hum (2017)
The main issue of this research isLove and Hope. Everyone who lives in the world has special things in themselves, it is just like love and hope. The purpose of this research is to analyze Love and Hope Reflected in Gayle Forman's If I Stay especially on the main character of this novel, Mia Hall based on an individual psychological approach. The reseacher used qualitative method. The reseacher used two data sources: primer and secondary. The primer data was If I Stay novel by Gayle Forman. The sources of secondary data are taken from other sources related the study, such as: website, dictionary, and some books which support the research. For collection data method, the reseacher used descriptive qualitative research. Based on this analysis, the researcher took some conclusions.This study shows that to achieve a dream is not easy. But, Mia proves to make her dream come true; it needs work hard, it is proven by playing cello and being good cellist the support and love of her parents.